2007
DOI: 10.1073/pnas.0609026104
|View full text |Cite
|
Sign up to set email alerts
|

Innate response to self-antigen significantly exacerbates burn wound depth

Abstract: A major component of burn injury is caused by additional local damage from acute inflammation. Using a scald burn model in mice, we find that this part of the injury is dependent on recognition of self-antigen by specific natural IgM, leading to activation of the complement system. We propose that the depth of a burn wound is a sum of the thermal energy applied and of the degree of host inflammatory response.complement ͉ natural IgM ͉ trauma ͉ wound physiology

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
44
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 29 publications
2
44
0
Order By: Relevance
“…Experiments in different animal burn models with either soluble complement receptor 1, an inhibitor of complement activation by both classical and alternative pathway, or C1 inhibitor showed that complement inhibition led to reduced neutrophil infiltration and reduced burn wound severity. [11][12][13]27 In addition to reduced tissue damage, local inhibition of inflammation may also reduce systemic complications. A recent study showed that attenuating burn wound inflammation by a locally administered p38 mitogen-activated protein kinase inhibitor improved survival in mice, 28 indicating that, indeed, attenuation of local burn wound inflammation may effect the systemic inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experiments in different animal burn models with either soluble complement receptor 1, an inhibitor of complement activation by both classical and alternative pathway, or C1 inhibitor showed that complement inhibition led to reduced neutrophil infiltration and reduced burn wound severity. [11][12][13]27 In addition to reduced tissue damage, local inhibition of inflammation may also reduce systemic complications. A recent study showed that attenuating burn wound inflammation by a locally administered p38 mitogen-activated protein kinase inhibitor improved survival in mice, 28 indicating that, indeed, attenuation of local burn wound inflammation may effect the systemic inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 In line with this, in complement factor C4 knock-out mice, burn wounds healed without contracture or scarring, whereas in burn wound healing in wild-type mice, scarring and contracture occurred. 13 Postburn blood levels of CRP were shown to be not only proportional with the extent of the burn wound area but also with the depth of the wound. 14,15 Interestingly, in nonburn wounds CRP was shown to activate complement locally on a tissue level in various inflammatory diseases, such as myocardial infarction 16 and atherosclerosis.…”
mentioning
confidence: 98%
“…Thus, they found that pretreatment with systemic N2 peptide (a peptide that binds IgM) or posttreatment with topical N2 peptide blocks inflammatory exacerbation of burn wound injury. 50 Once leukocytes are attracted to a site of burn injury, whether by complement breakdown products or other mediators, they adhere to the vascular endothelium through interactions between leukocyte surface receptors and specialized ligands on the endothelial surface. In a rabbit burn model, the effect of an antibody to CD18 (MAb 60.3) on wound healing was tested.…”
Section: Neutrophil Aggregation Venule Occlusion and Cytokine Produmentioning
confidence: 99%
“…However, the inflammatory cascade often goes uncontrolled and results in excessive production of proinflammatory cytokines, leading to local tissue edema, ischemia, and consequently progressive injury of burn wounds. 7,8 The essence of inflammation after burn or trauma is the activation of innate immunity. The immune system recognizes danger signals released from tissue injury or pathogens through pattern recognition receptors.…”
mentioning
confidence: 99%